2002
DOI: 10.1016/s0378-1097(02)01085-6
|View full text |Cite
|
Sign up to set email alerts
|

Models of 2,4,6-trinitrotoluene (TNT) initial conversion by yeasts

Abstract: The original models of the initial steps of 2,4,6-trinitrotoluene (TNT) conversion by yeasts are presented. Saccharomyces sp. ZS-A1 reduced nitro groups of TNT producing isomeric monohydroxylaminodinitrotoluenes (HADNT) as the key initial metabolites (molar ratio HADNT/TNT was up to 0.81), whereas aminodinitrotoluenes (ADNT) and the hydride^Meisenheimer complex of TNT (H-TNT) were the minor products. Conversely, Candida sp. AN-L13 transformed TNT almost quantitatively into H-TNT, thus realizing the alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…Some xenobiotic compounds have been the cause of massive pollution of most natural environments owing to the wide application of pesticides and herbicides in agriculture, as well as the use of additives or detergents in textile, printing and the iron–steel industries. Among them, trinitrotoluene (TNT) is considered one of the most dangerous xenobiotics known: Zaripov, Naumov, Abdrakhmanova, Garusov, and Naumova () reported that a few tolerant yeasts belonging to the genera Candida and Saccharomyces were found, although the authors did not specify the species. Biodegradation and bioconversion of xenobiotic compounds have been extensively used in agriculture but were globally banned from application starting from early 1980s.…”
Section: Major Factors In Extreme Habitats: Hard But Not Impossiblementioning
confidence: 99%
“…Some xenobiotic compounds have been the cause of massive pollution of most natural environments owing to the wide application of pesticides and herbicides in agriculture, as well as the use of additives or detergents in textile, printing and the iron–steel industries. Among them, trinitrotoluene (TNT) is considered one of the most dangerous xenobiotics known: Zaripov, Naumov, Abdrakhmanova, Garusov, and Naumova () reported that a few tolerant yeasts belonging to the genera Candida and Saccharomyces were found, although the authors did not specify the species. Biodegradation and bioconversion of xenobiotic compounds have been extensively used in agriculture but were globally banned from application starting from early 1980s.…”
Section: Major Factors In Extreme Habitats: Hard But Not Impossiblementioning
confidence: 99%
“…Although few studies on the mutagenicity of TNT have reported that nitroreductase and O-acetyltransferase were essential for expression of TNT mutagenicity [14,15], whether this is true for other nitroaromatics is unclear. On the other hand, many living organisms such as humans, plants, algae, yeast, microorganisms, and so on, commonly convert TNT into aminodinitrotoluenes and, in some cases, diaminonitrotoluenes [16][17][18][19][20][21][22]. We suggest that, for other * To whom correspondence may be addressed (ogawahi@life.kyutech.ac.jp).…”
Section: Introductionmentioning
confidence: 99%
“…The aromatic ring reduction of TNT allows the fission of the aromatic rings which opens up the possibility of TNT mineralization. However, only a few strains of bacteria (French et al 1998;Vorbeck et al 1998;Pak et al 2000;Kim et al 2002;van Dillewijn et al 2008;Wittich et al 2008) and fungi (Kim and Song 2000;Zaripov et al 2002;Jain et al 2004) were demonstrated to be capable of TNT transformation via aromatic ring reduction.…”
Section: Pathways Of Tnt Degradationmentioning
confidence: 99%
“…H + were identified. Subsequent studies have demonstrated that other microorganisms are also able to reduce the aromatic ring of TNT by hydride ion attack (French et al 1998;Kim and Song 2000;Pak et al 2000;Zaripov et al 2002;Jain et al 2004;Wittich et al 2008;Ziganshin et al 2010a, b).…”
mentioning
confidence: 99%
See 1 more Smart Citation